2005
DOI: 10.1016/j.jmaa.2005.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Numerical differentiation for two-dimensional scattered data

Abstract: In this paper, we propose a regularization method for numerical differentiation of two-dimensional mildly scattered input data. A regularized solution is constructed based on the Green's function. The existence and uniqueness of the regularized solution are proved and the convergence estimates are provided under a simple choice of regularization parameter. Numerical results show that our method is quite effective. One of the advantages for our proposed method is that the basis functions are independent of inpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 15 publications
0
9
0
2
Order By: Relevance
“…The main difficulty is that it is an ill-posed problem, which means small errors in the measurement of a function may lead to large errors in its computed derivatives [6,12]. A number of techniques have been developed for numerical differentiation [2,[8][9][10]12,[15][16][17][18][19][21][22][23]. However, most of the results given in these methods are corresponding to the functions with an inferior smoothness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main difficulty is that it is an ill-posed problem, which means small errors in the measurement of a function may lead to large errors in its computed derivatives [6,12]. A number of techniques have been developed for numerical differentiation [2,[8][9][10]12,[15][16][17][18][19][21][22][23]. However, most of the results given in these methods are corresponding to the functions with an inferior smoothness.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the results given in these methods are corresponding to the functions with an inferior smoothness. In [21,23], the convergence results corresponding to smooth scales of accurate functions in the Sobolev space have been obtained, but the methods are not self-adaptive. In order to obtain the corresponding convergence results, the methods have to be changed to fit the different smooth scales of the accurate functions.…”
Section: Introductionmentioning
confidence: 99%
“…A number of techniques have been well developed for numerical differentiation in one-dimensional case [6], [7], [9], [10], [14]. Besides, as far as we know, the literatures on noisy data in two dimensions are relatively poor [2], [12], [13]. In [14], we present a mollification method to deal with numerical differentiation in one-dimensional case.…”
Section: Introductionmentioning
confidence: 99%
“…For higher order derivatives in the one-dimensional case and for first order derivatives in two-dimensional case, numerical differentiation method along the line of this method were given in [13,15], respectively. For the twodimensional case, the new ingredient was that the variational problem for the regularized minimization problem is solved by using Green's function for the Laplacian with Dirichlet boundary condition and a scheme for computing the first order derivative was given in [15].…”
Section: Introductionmentioning
confidence: 99%
“…For the twodimensional case, the new ingredient was that the variational problem for the regularized minimization problem is solved by using Green's function for the Laplacian with Dirichlet boundary condition and a scheme for computing the first order derivative was given in [15]. The numerical example showed that this method was efficient.…”
Section: Introductionmentioning
confidence: 99%